Improvement of beef cattle through breeding methods - Smith, W.H.; Wheat, J.D.; Spies, H.; Gottlieb, H.A. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn cattle breeding program was continued during 1961 according to the breeding program initiated in 1949. Inbreeding of the two lines has been continued. The Wernacre Premier line is in its fourth generation, and the Mercury line will enter its fourth generation of inbreeding during 1962. The inbreeding plan has been basically to continue successive generations of half-sibbing in both lines.
Keywords: Beef; Inbreeding; Production traits